FRI0229 Survey on transportation and storage of biological therapies by patients. (15th June 2017) - Saavedra, M Arias; Aimo, C; Andrade, JJ Astudillo; Alvarez, D; Sequeira, G; Kerzberg, EM
Abstract : Background: in order to ensure the pharmacological action of thermolabile drugs, it is mandatory to keep the cold chain unbroken from manufacturing to administration since lack of observance of these rules may compromise their efficacy. (1, 2) Objectives: to ascertain key aspects of transportation and storage of Biological Therapy (BT) on the part of the patients. Methods: survey among outpatients who either were treated in the centre or attended the centre for the administration of a BT. Inclusion criteria encompassed patients of over 18 years of age, who were receiving a BT (at least one dose over the last 12 months) whose patient information leaflet indicated, "... must be refrigerated at 2°C to 8°C (36°F to 46°F). Do not freeze." The survey comprised 31 questions about transportation and storage of the BT from the moment of collection from the pharmacy to its administration. This study was approved by the Bioethics Committee. Every patient signed an informed consent form. Results: Eighty-three patients were interviewed (76% female and 24% males), their average age was 53 years old, 60% had Rheumatoid Arthritis, 24% Psoriatic Arthritis, and 16% sustained other conditions. Sixty-four percent were undergoing BT for the first time. Forty-eight percent were enrolled in a patient assistance programme. Had patients been fully informed of the importance of proper transportation and storage of the drug? No, 20% acknowledged that the first time they dealt with a BT, they had not been made aware of the relevance of its correct preservation. Are patients administered the BT immediately after collecting it from the pharmacy? No, 77% collected the drug at least 7 days before administration and though they received the BT in a cooler with ice packs (except in 5 cases) 71% was uninformed of how long it could be kept in this condition. Is the BT duly stored in the patient's refrigerator? No, 28% misplaced the drug (65% in the freezer), and 90% did not know the temperature range at which it should be kept in the fridge. Only 1 patient used a thermometer to control the appliance temperature. Is there another crucial point as to BT storage at home? Yes, 53% of the 83 patients had experienced frequent power cuts in summer; out of these, 59% on a weekly basis. Forty percent of the 83 patients had power cuts of over 12 hours, 28% of over 24 hours, and 22% of over 48 hours. Out of the 83 patients, 37% took the BT to another house to avoid wasting it, and 4 had to dispose of it due to a protracted power cut. Five patients were away from home for over 48 hours during which the BT was in the fridge and they had not assigned another person to take care of the drug during their absence. Is the BT removed from the fridge only for its immediate administration? No, 46% of the respondents travelled to a centre, half of them for over an hour, carrying the BT. Conclusions: before administering a BT, it is imperative to brief patients on suitable transportation and storage methods. Thus, treatment failure should prompt a thorough assessment of transportation and storage conditions. References: Allegra JR, Brennan J, Lanier V, Lavery R, Markenzie B. Storage temperatures of out-of-hospital medications. Acad Emerg Med. 1999;6:1098–103. Marco JL, Cuéllar MJ, Pérez-Castellό I, Castellό A, Muelas J, Pelegrí J. La cadena del frío de los medicamentos termolábiles en el domicilio del paciente. Pharm Care Esp. 2008;10:40–3. Disclosure of Interest: None declared